Ordinance No. 2, §§ 2-3 & 7, Soap Lake Town Council (1919) (Soap Lake, Washington). - (:unkn) unknown (My University, 1919)
That it shall be unlawful for any person to discharge any firearm or other dangerous weapon, at any place within the incorporated limits of the Town of Soap Lake.It shall be unlawful for any person to carry any firearm or other dangerous weapon, or to exhibit, flourish or to use the same in any manner having a tendency to put any other person in terror or fear; upon any of the public highways or other public places within the incorporated limits of the Town of Soap Lake...
Keywords: BRANDISHING; CARRY; DISCHARGE